Sustainability in Business Plans: a Portuguese Linen Textile Company case - Duarte de Almeida, I.; M.J. Delgado (1st International Conference on Design and Industry, 2024)
This article examines sustainability in the Textile Industry (TI) using Elkington's Triple Bottom Line (TBL) framework, emphasising People, Planet and Profit. The literature review examines the TBL pillars and emerging solutions to minimise environmental impacts in textile production. While circular economy (CE) practices alone are not enough to combat pollution and the effects of climate change, a second solution mentioned in the Literature Review is using natural fibres in the textile industry. These natural fibres offer a double advantage in TI: (i) sustainability benefits and (ii) a cleaner and greener industry. The EU Strategy for Sustainable and Circular Textiles underlines the importance of such initiatives and positions natural fibres as environmentally superior. This paper outlines a dual approach focusing on the linen sector as a case study. It concludes with a call for sustainable practices in the linen TI and presents an innovative business plan guided by the CE principles.